2015
DOI: 10.1097/mpa.0000000000000404
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Development of Diabetes Mellitus After Pancreatic Resection

Abstract: The resection volume of the pancreas is associated with a change in glucose homeostasis after pancreatectomy. Therefore, preservation of the pancreatic parenchyma is important to minimize the onset of DM in patients with a high pancreatic resected volume ratio (>35.6%) in DP, a high body mass index, or in old age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
61
2
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(71 citation statements)
references
References 22 publications
6
61
2
2
Order By: Relevance
“…This finding may be associated with our results, in which the pancreatic volume reduction at 6 and 12 months after PD is related to new onset DM. Similar results have been reported by Kwon et al [15] They described that the mean time interval between pancreatic resection and onset of DM was 16.8 months and suggested that careful analysis of glucose metabolism parameters is necessary, especially at approximately 16 months after pancreatic resection.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This finding may be associated with our results, in which the pancreatic volume reduction at 6 and 12 months after PD is related to new onset DM. Similar results have been reported by Kwon et al [15] They described that the mean time interval between pancreatic resection and onset of DM was 16.8 months and suggested that careful analysis of glucose metabolism parameters is necessary, especially at approximately 16 months after pancreatic resection.…”
Section: Discussionsupporting
confidence: 89%
“…There have been various results from studies on the occurrence of new onset DM after PD, with the incidence reported between 0% and 50%. [3,615] In this study, we report that PD led to glucose impairment, and postoperative NODM developed in 24.2% of nondiabetic patients who underwent PD. This result is consistent with the previous literature on the incidence of new onset DM after PD.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Sample sizes in individual studies ranged from 20 to 4775 patients, with a total of 9970 patients included for analysis. Table summarizes the study characteristics and key results for the included studies . These studies included 5636 patients undergoing pancreaticoduodenectomy, 3922 patients with distal pancreatectomy and 315 undergoing central pancreatectomy.…”
Section: Resultsmentioning
confidence: 99%
“…Some dogs develop transient hyperglycemia, whereas a smaller number of dogs develop persistent DM requiring long‐term administration of insulin . In human medicine, prevalence of postpancreatectomy DM varies from 5 to 78% depending on the heterogeneity of the population studied . The largest study revealed a median prevalence of 23% .…”
Section: Introductionmentioning
confidence: 99%